2017
DOI: 10.1111/eva.12477
|View full text |Cite
|
Sign up to set email alerts
|

Selection by higher‐order effects of salinity and bacteria on early life‐stages of Western Baltic spring‐spawning herring

Abstract: Habitat stratification by abiotic and biotic factors initiates divergence of populations and leads to ecological speciation. In contrast to fully marine waters, the Baltic Sea is stratified by a salinity gradient that strongly affects fish physiology, distribution, diversity and virulence of important marine pathogens. Animals thus face the challenge to simultaneously adapt to the concurrent salinity and cope with the selection imposed by the changing pathogenic virulence. Western Baltic spring‐spawning herrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…The adaptation to low-salinity conditions was even clearer at 35 psu, where fertilization rates of hybrids originating from 16 psu were very low (< 20%). This is consistent with a recent study of Poirier et al (2017), which also suggested that local adaptation to low salinity depends on the paternal origin. In contrast to their results, however, the hatching rates in our study were not influenced by any paternal or maternal origin or environmental conditions.…”
Section: Discussionsupporting
confidence: 93%
“…The adaptation to low-salinity conditions was even clearer at 35 psu, where fertilization rates of hybrids originating from 16 psu were very low (< 20%). This is consistent with a recent study of Poirier et al (2017), which also suggested that local adaptation to low salinity depends on the paternal origin. In contrast to their results, however, the hatching rates in our study were not influenced by any paternal or maternal origin or environmental conditions.…”
Section: Discussionsupporting
confidence: 93%
“…V. alginolyticus, a ubiquitous marine opportunistic pathogen can cause mass mortalities in shellfish, shrimp, and fish, resulting in severe economic losses worldwide [3,21,22]. Vibrio pathogenicity is a complex interaction of abiotic and biotic factors, including high temperatures [23,24] low salinities [25], host and bacterial genotypes [26,27]. To date only six closed alginolyticus genomes are available, while 28 remain fragmented with 2 to 75 contigs (last accessed: December 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Marine bacteria of the genus Vibrio are present along the coast of the Baltic Sea [20,21] and their abundance, genetic composition and virulence are related to environmental factors, including temperature and salinity [20,22,23]. Characteristic for this habitat is a salinity gradient ranging from almost freshwater in the North and East to nearly fully marine conditions at the transition to the North Sea [24].…”
Section: Introductionmentioning
confidence: 99%